Solar energy exploitation and storage in a novel hybrid thermo-electrochemical process with net-zero carbon emissions. (15th August 2022) - Ghorbani, Bahram; Wang, Wanrong; Li, Jie; Khatami Jouybari, Alireza; Monajati Saharkhiz, Mohammad Hossein
Abstract: The remarkable growth in global energy demand and greenhouse gas emissions necessitates the development of methods for efficient and reliable exploitation of sustainable and carbon-neutral energy sources. Chemical hydrogen storage is one of the efficient methods for converting renewable energy into valuable fuels for energy storage and transportation. This paper designs a novel hybrid process for simultaneous production of liquid methanol, ammonia, and heavy hydrocarbons using the combustion products of hydrocarbons emitted from industrial plants and methane. It mainly consists of several subprocesses including thermo-electrochemical cycle, CO2 capture, ammonia and liquid methanol production, and gas to liquid (GTL). CO2 is captured and utilized for the production of liquid methanol. Photovoltaic panels and parabolic trough collectors provide electrical and part of the thermal required in the process. The structure produces 17.95 kg h −1 methanol, 45.54 kg h −1 heavy hydrocarbons, and 20.44 kg h −1 ammonia. The thermal efficiencies of the methanol production cycle, GTL cycle, and the hybrid structure are 86.64%, 51.06%, and 15.00%, respectively. Exergy analysis indicates that photovoltaic panels have the maximum exergy destruction share (71.09%) followed by reactors (18.72%). Sensitivity analysis results show that the decline in the mass flow rate of methane from 9 to 5 kg h −1 leads to an increase in the integrated structure's total thermal and exergy efficiencies to 18.28% and 28.54%, respectively. Besides, a decrease in the mass flow rate of CO2 from 30 to 10 kg h −1 raises the exergy efficiency of the integrated structure to 21.99%. The methanol production rate and exergy efficiency of the methanol production cycle are reduced to 6.932 kg h −1 and 34.62%. Graphical abstract: Unlabelled Image Highlights: A novel system for the trigeneration of methanol, heavy hydrocarbons & NH3 was developed. Integrated thermo-electrochemical cycle, GTL plant, NH3 & methanol production cycles. Solar collectors & PV panels were used for supplying the system's required energy demand. The thermal efficiencies of the GTL cycle & the structure were 51.06% &15%. The total exergy efficiency & irreversibility of the structure were 20.92% & 3195 kW.